2007
DOI: 10.1007/s11103-007-9207-2
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor induced activation of the methylerythritol phosphate pathway toward phytoalexins biosynthesis in rice

Abstract: Diterpenoid phytoalexins such as momilactones and phytocassanes are produced via geranylgeranyl diphosphate in suspension-cultured rice cells after treatment with a chitin elicitor. We have previously shown that the production of diterpene hydrocarbons leading to phytoalexins and the expression of related biosynthetic genes are activated in suspension-cultured rice cells upon elicitor treatment. To better understand the elicitor-induced activation of phytoalexin biosynthesis, we conducted microarray analysis u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
136
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(148 citation statements)
references
References 44 publications
(48 reference statements)
12
136
0
Order By: Relevance
“…15) The following oligonucleotide sequences were used: Ubiquitin, functions as a repressor, we speculate that the activation of defense-related genes by overexpressed OsWRKY71 is indirect. In a previous microarray analysis using suspension-cultured rice cells treated with chitin oligosaccharide elicitor, 21) it was found that the mRNA levels of genes encoding the above chitinases, PR-5, and peroxidases showed changes similar to that of OsWR-KY71, or delayed changes, further confirming the involvement of OsWRKY71 in the activation of defense-related genes.…”
Section: Gal4db-oswrky71mentioning
confidence: 81%
See 2 more Smart Citations
“…15) The following oligonucleotide sequences were used: Ubiquitin, functions as a repressor, we speculate that the activation of defense-related genes by overexpressed OsWRKY71 is indirect. In a previous microarray analysis using suspension-cultured rice cells treated with chitin oligosaccharide elicitor, 21) it was found that the mRNA levels of genes encoding the above chitinases, PR-5, and peroxidases showed changes similar to that of OsWR-KY71, or delayed changes, further confirming the involvement of OsWRKY71 in the activation of defense-related genes.…”
Section: Gal4db-oswrky71mentioning
confidence: 81%
“…15) As for the results of microarray analysis, a total of 64 genes were down-regulated, and 21 genes of the 64 genes were also down-regulated by chitin oligosaccharide elicitor treatment. 21) One-third of the 21 down-regulated genes are of unknown function, and the other two-thirds included genes likely to be related to metabolism, regulation of gene expression, and signal transduction, but the biological functions of these down-regulated genes in defense responses remain unknown. On the other hand, a total of 200 genes were up-regulated in the OsWR-KY71-overexpressing transgenic rice cells, and 146 of the 200 up-regulated genes were also up-regulated by chitin oligosaccharide elicitor treatment.…”
Section: Gal4db-oswrky71mentioning
confidence: 99%
See 1 more Smart Citation
“…Since momilactones A and B were first discovered by Kato et al (1973), major research has been conducted on the two compounds concentrated on plant growth and pathogen (Fukuta et al 2007;Okada et al 2007;Hasegawa et al 2010), and antioxidant capacity (Fukuta et al 2007), cytotoxic and antitumor activity (Kim et al 2007), whereas other biological activities of momilactones A and B have remained unknown. This study is the first to demonstrate that momilactones A and B correlated to the tolerance of drought and salinity in much stronger levels than the weed tolerance in rice.…”
Section: Correlation Coefficientsmentioning
confidence: 99%
“…1) against the fungal rice blast disease pathogen Magnaporthe oryzae in rice leaves and straw (Cartwright et al 1977(Cartwright et al , 1981. The function of momilactone A as a phytoalenxin was extensively studied against fungal pathogens (Fukuta et al 2007;Okada et al 2007;Hasegawa et al 2010), whereas momilactone B was much less described (Fukuta et al 2007). Among potential growth inhibitors detected in rice including phenolic acids, fatty acids, phenylalkanoic acids, hydroxyamic acids, terpenes, and indoles, momilactones A and B particularly play a critical role (Kato-Noguchi and Peters 2013).…”
Section: Introductionmentioning
confidence: 99%